The relationship between imposed accountability and elective accountability on corporate zakat payment among Malaysian Shariah Compliance Company: A proposed study - Ab Rahman, Siti Maziah (Journal of Islamic, Social, Economics and Development, 2025)
Zakah is one of the main religious dues in Islam. Zakah does not only purify one’s wealth but also a mechanism to uplift the socio-economy of the ummah. Zakah is one of the five pillars of the Islamic faith, which is an obligatory form of “charity”, and every Muslim is expected to contribute. The use of zakah is not only to purify property but to purify the hearts of zakah payers from selfishness and wealth greed. According to National Fatwa Committee, business entities that formed the principle of syakhsiyyah i’tibariyyah (legal entity) are obliged to pay zakah under the principle of khultah (group ownership). However, factors that influence a business entity’s zakah payment are still not properly defined, and very limited research done on this. Malaysian zakah institution still faces several obstacles to increasing the collection of business zakat. Most of the previous studies on this issue they do not in more detail about the factor of imposed accountability, and elective accountability. Hence, the purpose of this research is to propose a conceptual framework on corporate zakat payment decisions. This research also applies Institutional work theory (IWT). The aim of this research is to identify business zakah payment influencing factors in business entities and take Shariah Compliance Companies as research subjects and decision makers on behalf company in Shariah Compliance Companies as a research object.